Autores - atores: perejivanie no contexto teatral - Salvador, Francisca Nunes da Mota (2021)
This study is supported by the Vigotskian theoretical foundation from the perspective of the Socio-Historical-Cultural Theory and the concept of perejivanie, based on the discussions of Stanislavski ([1961]2012; [1936]2014) and Vigotski ([1933-34]2006), among other recent researchers. It aims, in general, to understand the ways in which experiences with the theater, at a specific place – the Instituto Dinâmico –, impact the development of the Authors-Actors participating in the project regarding the transformation of themselves in the relationship with others in the context in which they are inserted. It aims, in a specific way, to identify conflict situations in dramatic events that emerge from the testimonies of the Authors-Actors; Identify the impact of these reported situations on the lives of the Authors-Actors. For this, it is a guiding question: How are dramatic events characterized as propellers of learning and critical development of participants? This study is supported theoretically and methodologically at PCCol – Critical Collaborative Research (MAGALHÃES, 2012, 2014) for its activist and interventionist characteristics and for the central focus on collaborative relationships in and for the critical development of all participants including the researcher. Developed in a private company located in the city of Alfredo Chaves (ES), which offers to Elementary and High School students, reading and production projects integrated with the scenic art, the corpus was constituted from statements produced by the participating Authors-Actors, during their experiences in the theatrical context. The data was produced through sessions that were videotaped and transcribed, then analyzed based on the categories of argumentation (LIBERALI, 2013, 2016). The results reveal new ways of acting, as well as overcoming of affection-cognitive conflicts in dramatic events emerging from the participants' collective relations with the theater at the Instituto Dinâmico. Thus, they reveal the ways in which the moments of perejivanie (experience) are characterized as propellers of learning and critical development of all participants, Authors-Actors and Professor-Researcher